Artificial Intelligence and specialized software: integrating strategies for resilient planning and urban environmental management - Campoy, Carlos Quedas; Souza , Amanda Maria Rabelo; Izidoro, Cleide (Scientific Journal ANAP, 2025)
Objective – This paper aims to critically analyze the potential of integrating artificial intelligence technologies and specialized software as strategies to enhance resilient urban planning and environmental management in the face of climate change. Methodology – The study is based on a literature review and an analytical survey of advanced digital tools, focusing on urban applications. Originality/Relevance – It addresses the theoretical gap concerning the integrated application of artificial intelligence to tackle the high dimensionality of complex urban data, proposing innovative and replicable methodological approaches. Results – The study finds that such technologies enable predictive simulations, the generation of adaptive spatial solutions, and support strategic decision-making, reducing analytical complexity and improving planning effectiveness. Theoretical/Methodological Contributions – The article offers an integrated and flexible methodological framework, with practical guidelines and technical-scientific foundations applicable to sustainable urban governance. Social and Environmental Contributions – The proposed solutions foster community inclusion, promote more resilient cities, and support the mitigation of severe environmental impacts.